Living donor liver transplantation in an infant patient with progressive familial intrahepatic cholestasis along with hepatocellular carcinoma: a case report - Jung-Man Namgoong; Shin Hwang; Dae-Yeon Kim; Chul-Soo Ahn; Hyunhee Kwon; Suhyeon Ha; Kyung Mo Kim; Seak Hee Oh (Korean Journal of Transplantation, 2022)
Progressive familial intrahepatic cholestasis (PFIC) is an autosomal recessive inherited disease requiring liver transplantation (LT). Hepatocellular carcinoma (HCC) is very rare in infants. We present a case of living donor LT using a left lateral section graft performed in a 7-month-old female infant diagnosed with PFIC type II and HCC. No mutation on ABCB11 gene was identified. Because of progressive deterioration of liver function, living donor LT with her mother’s left lateral section graft was performed. Pretransplant serum alpha-fetoprotein (AFP) level was increased to 2,740 ng/mL, but HCC was not taken into account because of its rarity. The explant liver showed micronodular liver cirrhosis, multiple infantile hemangiomas and two HCCs of 0.7 cm and 0.3 cm in size. The patient recovered uneventfully from the LT operation. This patient has been regularly followed up with abdomen ultrasonography and AFP measurement every 6 months. The patient has been continually doing well for 8 years after the LT. In conclusion, LT is currently the only effective treatment for PFIC-associated end-stage liver diseases. HCC can develop at the cirrhotic liver of any cause, thus elevation of HCC tumor markers in pediatric patients is an important clue to perform further investigation before LT.